A matter of faith religion in the 2004 presidential election - Campbell, David E., 1971-; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2007)
"Examines the religious affiliations of voters and party elites and evaluates the claim that moral values were decisive in the 2004 election. Analyzes strategies used to mobilize religious conservatives and examines the voting behavior of a broad range of groups, including evangelicals, African Americans, and the religious left"--Provided by publisher.
The 2004 election : a matter of faith? / David E. Campbell -- How the faithful voted : religious communities and the presidential vote / John C. Green, Lyman A. Kellstedt, Corwin E. Smidt, James L. Guth -- Faithful divides : party elites and religion / John C. Green and John S. Jackson -- Moral values : media, voters, and candidate strategy / D. Sunshine Hillygus -- Evangelicals and moral values / Scott Keeter -- Microtargeting and the instrumental mobilization of religious conservatives / J. Quin Monson and Baxter Oliphant -- The case of Bush's reelection : did gay marriage do it? / David E. Campbell and J. Quin Monson -- Stem cell research / Barbara Norrander and Jan Norrander -- The changing Catholic voter : comparing responses to John Kennedy in 1960 and John Kerry in 2004 / J. Matthew Wilson -- George W. Bush and the evangelicals : religious commitment and partisan change, 1960-2004 / Geoffrey C. Layman and Laura S. Hussey -- Latinos and religion / David L. Leal -- The Black church : maintaining old coalitions / Eric L. McDaniel -- A gentle creek or a "river glorious"? : the religious left in the 2004 election / Lyman A. Kellstedt, Corwin E. Smidt, John C. Green, and James L. Guth -- From event to theory : a summary analysis / David C. Leege.
Chiefly papers presented at a conference sponsored by the University of Notre Dame's Program in American Democracy in December 2005.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: United States. -- Congress -- Elections, 2004.; Presidents -- United States -- Election -- 2004.; Christianity and politics -- United States; United States -- Politics and government -- 2001-; Electronic books